2018
DOI: 10.1002/adma.201806761
|View full text |Cite
|
Sign up to set email alerts
|

An Oxygen‐Vacancy‐Rich Semiconductor‐Supported Bifunctional Catalyst for Efficient and Stable Zinc–Air Batteries

Abstract: The practical application of rechargeable zinc-air batteries requires a low-cost, efficient, and stable air electrode catalyst toward both the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The most promising nonprecious bifunctional catalysts are carbon-supported transition metal hybrid materials. [1] However, carbon-supported catalysts suffer from carbon electrochemical oxidation, which causes the loss or aggregation of supported catalysts and degrades the electrocatalysis durability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(83 citation statements)
references
References 50 publications
0
83
0
Order By: Relevance
“…The C dl was calculated from double-layer charging curves in a non-faradic potential range of 1.1-1.3 V (versus RHE) and using the following equation in which i c and ʋ are charging current (mA cm −2 ) and scan rate (mV s −1 ), respectively [6][7][8][9][10] : The electrocatalytic performances for ORR and OER reactions were measured in a three-electrode cell at standard temperature and pressure conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The C dl was calculated from double-layer charging curves in a non-faradic potential range of 1.1-1.3 V (versus RHE) and using the following equation in which i c and ʋ are charging current (mA cm −2 ) and scan rate (mV s −1 ), respectively [6][7][8][9][10] : The electrocatalytic performances for ORR and OER reactions were measured in a three-electrode cell at standard temperature and pressure conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The MPZ battery provides an open circuit voltage (OCV) of 1.47 V that is higher than PI battery (1.35 V) and PZ battery (1.37 V, Figure 5b), indicating lower catalytic activation loss. 2019, 9,1900911 evidencing the fast kinetics of oxygen reactions. Some turbulences are observed in the polarization curve during charging due to vigorous oxygen bubble coa lescence at high current densities.…”
Section: Electrochemical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, owing to the oxygen vacancies and the unique structure design, the catalyst achieved excellent electrochemical performance in Zn–air batteries. In addition, Chen and co‐workers reported that the oxygen vacancy defects can not only improve the conductivity of the oxide supports but also provide a stronger metal–support interaction (SMSI), so that the catalyst has a smaller metal size, higher catalytic activity, and higher stability for Zn–air batteries . Chou et al prepared CaMnO 3 nanotubes with abundant oxygen vacancies through calcination and sulfurization treatment.…”
Section: Defective Electrode Materials For Rechargeable Batteriesmentioning
confidence: 99%
“…Oxygen evolution reaction (OER: 4OH − → O 2 + 2H 2 O + 4e − ) has received wide attention recently because of its vital role in renewable energy devices, such as rechargeable Zn–air batteries and Li–O 2 batteries . An effective electrocatalyst is a necessity during the OER because it involves a stepwise four‐electron transfer at a high overpotential .…”
mentioning
confidence: 99%